Economic Consequences of Numerical Adaptation - Garagnani, Michele; Vieider, Ferdinand M. (Psychological Science, 2025)
Resource constraints in neural information processing imply that numerical discriminability optimally adapts to the frequency of numerical magnitudes in a decision maker’s environment. Here, we tested the economic consequences of efficient numerical range adaptation in representative samples of the United Kingdom and Japan ( N = 2,309) and in a replication in Austria and Hungary ( N = 607). We exploited natural variation in currency units and combined it with an orthogonal variation in experimental currency units to detect the effect of habitual versus nonhabitual numerical ranges on the incidence of errors in decisions under risk. The results highlight the direct economic importance of numerical adaptation, thus calling into question standard assumptions that choice quantities are perceived without noise.